2016
DOI: 10.4238/gmr.15027384
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of ERCC1 and ERCC2 genes involved in the nucleotide excision repair pathway influences the treatment outcome of gastric cancer

Abstract: ABSTRACT. We conducted a prospective study to investigate whether ERCC1 rs11615 and rs3212986 and ERCC2 rs13181 and rs1799793 gene polymorphisms could serve as potential biomarkers for the prognosis of gastric cancer. Between January 2010 and December 2012, 246 patients with pathologically proven gastric cancer who were receiving platinum-based chemotherapy were recruited from the First Affiliated Hospital of Guangxi Medical University. The genotyping of the gene polymorphisms was conducted using the polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The main characteristics of included studies are presented in Table 2 . 13 22 The distribution of genotypes in the control groups of all studies was in agreement with HWE except three. 18 , 20 , 21 A total of 10 studies were performed in Chinese populations.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The main characteristics of included studies are presented in Table 2 . 13 22 The distribution of genotypes in the control groups of all studies was in agreement with HWE except three. 18 , 20 , 21 A total of 10 studies were performed in Chinese populations.…”
Section: Resultssupporting
confidence: 67%
“…This was inconsistent with the conclusion of some previous studies. Zheng et al 13 have reported that the AA genotype of ERCC1 rs3212986 was associated with lower rates of complete remission and partial remission following chemotherapy in GC patients. Similarly, Bai et al 16 discovered that patients carrying the GT and TT genotypes of rs3212986 showed a significantly poorer response to chemotherapy than did those carrying the GG genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have reported a relationship between ERCC2 rs13181 and rs1799793 polymorphisms and chemotherapy efficacy in gastric cancer patients [12–24]. In 2014, a study by Yu et al revealed that the AA genotype of the ERCC2 rs1799793 polymorphism is associated with better response to chemotherapy in gastric cancer patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many researchers have investigated possible relationships between two ERCC2 polymorphisms, rs13181 and rs1799793, and treatment response and prognosis, which are indicators of chemotherapy efficacy, in patients with gastric cancer [12–24]; however, most of these studies have been inconclusive. Therefore, this meta-analysis was conducted to evaluate the abovementioned relationships.…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not find any direct association of the rs4134822 and rs1799793 with NMSC risk after covariates adjustment. Previously, many studies have focused on the association between NER gene and some other diseases, including prostate cancer [ 19 ], gastric cancer [ 20 ] and thyroid cancer [ 21 ]. Several studies [ 11 15 ] were also performed on association between SNPs within NER gene and NMSC risks, but the limited number for these articles could not concluded a consistent result on this association, and could not clarify the mechanism between NER gene and NMSC susceptibility.…”
Section: Discussionmentioning
confidence: 99%